Pedagogical Competencies and Classroom Anxieties in Teaching General Music - Pestano, Rayvin D.; Ibarra, Flrorante P. (Indonesian Research Journal in Education |IRJE|, 2021)
This study utilized a descriptive correlational research design to examine the pedagogical competencies and classroom anxieties in teaching general music of 50 public junior high school MAPEH (Music, Arts, Physical Education & Health) teachers in Gapan City, Philippines. Quantitative data were gathered using questionnaire as the main instrument involving statements measured through Likert scale. With a six-month data gathering, Pearson r was utilized in the analysis. Results disclosed that musical skills and knowledge were significantly correlated with pedagogical competencies and classroom anxieties in teaching general music. Recommendations on capacitating MAPEH teacher’s musical skills and knowledge must be considered to further improve the quality of music education.